Penerapan Relaksasi Otot Progresif Pada Pasien Hipertensi Dengan Masalah Keperawatan Nyeri Akut Pada Ny. N Di Wilayah Kerja UPT Puskesmas Medan Sunggal - Zhafira Aliefanny; Mona Hastuti (STIKES Columbia Asia Medan, 2025)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg or diastolic blood pressure of more than 90 mmHg. Hypertension is not only at high risk of suffering from heart disease, but also suffering from other diseases such as nerve, kidney, and blood vessel diseases and the higher the blood pressure the greater the risk, Signs and symptoms of hypertension that are often felt are dizziness, sleep disturbances, blurred vision, and headaches. One of the non-pharmacological treatments that can be done for hypertension sufferers is progressive muscle relaxation. The purpose of this paper is to discuss progressive muscle relaxation therapy for lowering blood pressure in hypertensive patients. The writing method uses a descriptive design with a nursing process approach. The results of the writing show that there is a decrease in blood pressure after progressive muscle relaxation therapy is carried out for 5 days, the results obtained before 150/80 mmHg and after 120/80 mmHg.